2019
DOI: 10.1111/1471-0528.15700
|View full text |Cite
|
Sign up to set email alerts
|

Maternal near‐miss and death among women with rupture of the gravid uterus: a secondary analysis of the Nigeria Near‐miss and Maternal Death Survey

Abstract: Objective To investigate the burden of maternal near-miss and death due to rupture of the gravid uterus, the indicators of quality of care, and avoidable factors associated with care deficiencies for ruptured uterus in Nigerian tertiary hospitals.Design Secondary analysis of a nationwide cross-sectional study.Setting Forty-two tertiary hospitals.Population Women admitted for pregnancy, childbirth or puerperal complications.Methods Cases of severe maternal outcome [SMO: maternal nearmiss (MNM) or maternal death… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The percentage of women reporting receiving any ANC was 67% and women receiving four or more visits was 57% [11]. Further, access to Emergency Obstetric Care (EmOC) in Nigeria is insufficient [14] and financial and geographical access barriers prevail [15,16]. Cultural beliefs and negative attitudes towards CS are other possible explanations for a delay in care-seeking behaviour and low CS rate [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…The percentage of women reporting receiving any ANC was 67% and women receiving four or more visits was 57% [11]. Further, access to Emergency Obstetric Care (EmOC) in Nigeria is insufficient [14] and financial and geographical access barriers prevail [15,16]. Cultural beliefs and negative attitudes towards CS are other possible explanations for a delay in care-seeking behaviour and low CS rate [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…8,10 Other factors responsible for the high incidence in developing countries relate to poverty, low literacy levels, potentially harmful cultural and religious practices, poor transportation and communication systems, not registering for antenatal care and high level of patronage of spiritual churches for pregnancy and child birth care. 7,14,16 These factors continue to increase the incidence of ruptured uterus in developing countries. It was also found that the majority of these patients in this study were unbooked (71.8%), this is comparable to the figures from other parts of the country and other countries in Sub-sahara Africa.…”
Section: Discussionmentioning
confidence: 99%
“…This agrees that ignorance and poverty contribute greatly to the high incidence of ruptured uterus seen in developing countries including Nigeria. 11,14,16 There exist some variations in the aetiological classification of ruptured uterus by different authours. 1 The commonest risk factors for ruptured uterus in this study were obstructed labour without a previous scar 19 (48.7%), followed by obstructed labour due to malpositions malpresentations/foetal macrosomia 9 (23.0%) and previous scar 7 (17.9%).…”
Section: Discussionmentioning
confidence: 99%
“…The adverse maternal outcomes of interest in the study were maternal near-miss, massive transfusion, hysterectomy, intensive care unit (ICU) admission, and deaths before discharge, and perinatal outcomes were stillbirth and neonatal deaths before delivery woman discharge. The criteria for maternal near-miss were based on the organ failure criteria recommended by the WHO [29]. Massive transfusion was de ned as transfusion of ≥ 1000 ml of whole blood or ≥ 5 units of red blood cell suspension [30].…”
Section: De Nition Of Variablesmentioning
confidence: 99%